2010
DOI: 10.1056/nejmoa0911781
|View full text |Cite
|
Sign up to set email alerts
|

Target Ranges of Oxygen Saturation in Extremely Preterm Infants

Abstract: Background-Previous studies have suggested that the incidence of retinopathy is lower in preterm infants with exposure to reduced levels of oxygenation than in those exposed to higher levels of oxygenation. However, it is unclear what range of oxygen saturation is appropriate to minimize retinopathy without increasing adverse outcomes.Methods-We performed a randomized trial with a 2-by-2 factorial design to compare target ranges of oxygen saturation of 85 to 89% or 91 to 95% among 1316 infants who were born be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
276
3
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 795 publications
(285 citation statements)
references
References 26 publications
4
276
3
2
Order By: Relevance
“…Despite several large randomised trials,32, 33, 34 the optimal SpO 2 range to reduce risk of ROP, while optimising survival, remains unclear. A recent post‐hoc analysis of data from two trials found that a target range of 85–89%, versus 91–95%, resulted in significantly increased risks of death or disability at 2 years and death alone 37.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite several large randomised trials,32, 33, 34 the optimal SpO 2 range to reduce risk of ROP, while optimising survival, remains unclear. A recent post‐hoc analysis of data from two trials found that a target range of 85–89%, versus 91–95%, resulted in significantly increased risks of death or disability at 2 years and death alone 37.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the best available evidence to balance risks of ROP and mortality at the time of this study,32, 33, 34 target ranges for term and preterm neonates were established in collaboration with Kenyan paediatricians and nurses, which advised values of SpO 2  ≥ 92% for neonates ≥34 weeks and SpO 2 89–93% for neonates <34 weeks. A training package was provided to staff prior to study implementation, which covered the use of the Lifebox and neonatal probe,29, 30 target ranges and oxygen management using available resources.…”
Section: Methodsmentioning
confidence: 99%
“…In drawing up the treatment guideline we used the premise that hypoxia and hyperoxia are risk factors for an adverse outcome in the preterm infant and should be avoided [10,11,12,13,14,15]. In addition to NIRS assessment of the cerebral circulation, a number of other techniques, particularly echocardiography, are used to assess the neonatal transitional circulation and related outcomes [1,16,17,18,19,20,21,22,23,24,25,26,27].…”
Section: Interventions That Affect Oxygen Delivery To the Brainmentioning
confidence: 99%
“…The first step would be decrease Fi O 2 in case Sa O 2 is above the normal range or high, even in the normal range [11,12,13,14,15]. Additional interventions would be to decrease mean airway pressure [26,75].…”
Section: Interventions That Affect Oxygen Delivery To the Brainmentioning
confidence: 99%
“…A National Institute of Child Health and Development (NICHD) Neonatal Research Network trial (8), as well as a study by Vento et al (9), previously demonstrated a possible pathogenic interaction between ROP and BPD, at least by means of oxygen exposure.…”
Section: Introductionmentioning
confidence: 99%